Análise da segurança estrutural em vigas de concreto armado de uma edifica- ção no município de Itaituba - PA - (:unkn) unknown (Universidade Federal do Oeste do Pará, 2023)
The reinforced concrete structures in Brazil must follow the corresponding design, execution and performance standards, following the guidelines of NBR 6118 (2014), aiming at the safety and comfort of users, to obtain a good use of the building. When cracks or fissures appear in a building, they must be analyzed in order to verify if these pathologies can compromise the service limit state or ultimate limit state of the concrete structure. This paper aims to analyze the development of typical flexural and shear cracks in reinforced concrete beams in a building used by an educational institution in the city of Itaituba-PA, allowing a diagnosis about their structural safety, as well as the reasons that led to the emergence of such pathologies. To achieve the proposed objectives, visits were made to the building studied, using the sclerometer and pacometer, allowing comparison of whether the execution of the structure followed what was presented in the structural project. In addition, computational analyses were performed with the aid of commercial software, enabling to verify whether the structural design was in accordance with the recommendations of NBR 6118 (2014). Based on the analyses performed, it was verified that the execution followed what was presented in the structural project and that it did not meet several criteria established by the Brazilian standard, with the need for an intervention to reinforce the reinforced concrete structure in order to ensure the structural safety of the building.
Keywords: Estruturas; Segurança; Cisalhamento; Estrutural.; CNPQ:: CIÊNCIAS EXATAS E DA TERRA